2021
DOI: 10.1371/journal.pone.0260677
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance among invasive Neisseria meningitidis isolates in England, Wales and Northern Ireland (2010/11 to 2018/19)

Abstract: Invasive meningococcal disease (IMD), caused by Neisseria meningitidis, can have a fatality rate as high as 10%, even with appropriate treatment. In the UK, penicillin is administered to patients in primary care whilst third generation cephalosporins, cefotaxime and ceftriaxone, are administered in secondary care. The first-choice antibiotic for chemoprophylaxis of close contacts is ciprofloxacin, followed by rifampicin. Immunocompromised individuals are often recommended antibiotic chemoprophylaxis and vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
17
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 51 publications
9
17
3
Order By: Relevance
“…No isolate was found nonsusceptible or resistant to ceftriaxone, meropenem, chloramphenicol, or rifampin. These results agree with previous studies that showed reduced susceptibility to penicillin among invasive isolates ( 7 9 , 13 , 14 ), suggesting that penicillin might not be suitable to treat IMD cases in Japan. However, we could not clarify the reason for the observation in this study, and it might have been associated with the antibiotic choice for the treatment of bacterial meningitis in Japan.…”
Section: Observationsupporting
confidence: 92%
See 2 more Smart Citations
“…No isolate was found nonsusceptible or resistant to ceftriaxone, meropenem, chloramphenicol, or rifampin. These results agree with previous studies that showed reduced susceptibility to penicillin among invasive isolates ( 7 9 , 13 , 14 ), suggesting that penicillin might not be suitable to treat IMD cases in Japan. However, we could not clarify the reason for the observation in this study, and it might have been associated with the antibiotic choice for the treatment of bacterial meningitis in Japan.…”
Section: Observationsupporting
confidence: 92%
“…This indicates, for the first time, that the penicillin-resistant invasive serogroup W, ST-11 CC lineage circulating in several countries ( 5 , 6 ) has already emerged in Japan. Three penicillin and ciprofloxacin-resistant isolates, NIID576, NIID614, and NIID620, recovered from individuals in different prefectures, were classified as the same nontypeable serogroup ST-32 CC strains harboring both penA33 (identified previously in penicillin-nonsusceptible strains) ( 14 ) and gyrA376 with a T91I substitution responsible for ciprofloxacin resistance ( Fig. 1 ).…”
Section: Observationmentioning
confidence: 89%
See 1 more Smart Citation
“…8,11 Moreover, increased prevalence of antibiotic resistance among N. meningitidis isolates worldwide, including Muslim-majority countries, is concerning. [12][13][14]…”
Section: Discussionmentioning
confidence: 99%
“…N. meningitidis resistance to 3GCs is rare, and only 1 cefotaxime-resistant isolate has been reported in the United Kingdom ( 12 ). In recent years, Pen NS meningococci have become more frequent worldwide ( 13 , 14 ), but data for meningococci from China with Pen NS and 3GCs resistance remain poorly described.…”
mentioning
confidence: 99%